Primary Palliative Care Education for Graduate Medical Trainees: Impacts and Needs. (April 2023) - Pennarola, Adam; Yoshioka, Tammy; Shah, Dhruvi; Larson, Sharon
As demand for palliative care (PC) services rise, there are insufficient numbers of PC specialists to provide PC for the US population. "Primary palliative care" refers to PC services that are administered by non-specialist PC providers. Educating trainees in graduate medical education (GME) programs is 1 strategy for expanding primary palliative care, though questions remain regarding the impact of PC education for GME trainees and where additional education is needed. This study is a multicenter, cross-sectional, web-based survey study of GME trainees assessing the needs for and impacts of primary palliative care education. The survey assessed the implementation of and participants' confidence with fundamental PC skills. The survey also asked about prior exposure to PC education and for participants' beliefs regarding areas that would be particularly helpful for future education. 170 residents and fellows from diverse training backgrounds participated in the survey out of 851 potential participants (response rate 19.98%). Exposure to PC education was associated with higher confidence and increased frequency of implementation of fundamental PC skills. Of the forms of education that were assessed, clinical/experiential education was associated most often with higher confidence and higher frequency of use of PC skills. Discussing goals of care, pain management for seriously ill patients, and communicating difficult information were those skills most frequently identified as important for additional training. This study demonstrates that by improving existing PC education or increasing access to PC education for GME trainees, it may be possible to improve primary palliative care.